Aspirin desensitization in nonsteroidal anti-inflammatory exacerbated respiratory disease: The first prospective cohort in Chile - Siña, María Josefina; Valdés, Felipe; Zelada, Úrsula; Tagle, María Teresa; Campillay, Rolando; Sandoval, Daniela; Herrera, Pablo; Bastías, Carla (Frontiers in Allergy, 2023)
Background Nonsteroidal anti-inflammatory exacerbated respiratory disease (N-ERD) is characterized by the Samter triad: chronic rhinosinusitis with nasal polyps, asthma, and nonallergic hypersensitivity to NSAIDs. Its diagnosis is based on a complete clinical history and an aspirin (ASA) challenge test. Medical treatments include biological drugs and ASA desensitization. Objective This study aims to evaluate the clinical response of patients with N-ERD undergoing functional endoscopic surgery (FES), followed by ASA desensitization and maintenance treatment, being the first prospective cohort study carried out in Chile. Methods We conducted 1-year follow-up of 12 patients with N-ERD treated with FES, desensitization, and maintenance with ASA. For each control, the medication score, sinonasal symptomatology (SNOT-22), PEF (peak expiratory flow), nasal polyposis (Lildholdt score), and the appearance of adverse effects were recorded. Computed tomography (CT) of the paranasal cavities was performed at baseline and at the 12-month follow-up to calculate the Lund–Mackay score. Results Patients presented a reduction of SNOT-22 after the FES, which was maintained at 12 months (p = 0.002); the symptoms that showed the greatest reduction were feeling embarrassed and nasal obstruction. The Lildholdt score was also significantly reduced (p = 0.001); in only three patients, the nasal polyps recurred, and all were small. The PEF showed a slight nonsignificant increase of 3.3%. In total, 75% of patients had an adverse effect, the most frequent being abdominal pain (66.7%), but none of the 12 patients required discontinuation of aspirin treatment in 1-year follow-up. The Lund–Mackay score had a significant reduction of 6.6 points (p < 0.001). Conclusion ASA desensitization is safe and effective in reducing upper and lower respiratory symptoms in patients with N-ERD and delays the reappearance of nasal polyps, although it is not exempt from adverse effects, with the vast majority being mild.